ReIndustrializing Architecture. (June 2016) - Yanagawa, Kane
After decades of improving the efficiency and economy of our existing building ecology, instruments of the Third Industrial Revolution are redefining the practice of architecture, both internally and externally. This article focuses on the employment of the Constrained Design Hysteresis methodology as a mediating strategy, in which computational tools for content creation and fabrication can merge in post-industrial societies to effectively reindustrialize the fields of architectural design manufacturing and building. Such reformation of the accepted norms of architectural building practice do not represent a regression of the profession to a pre-industrial mode of building craftsmanship, but an evolution into one that directly addresses various shortcomings of global industrialization, ranging from restrictions imposed by mass production to the creation of social class disparity. In this context, the application of computational tools and processes can both empower and liberate design individuals through the restructuring of the existing industrial manufacturing ecosystems.